Using conjoint analysis to understand customer preferences in customized low-income housebuilding projects - Hentschke, Cynthia dos Santos (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
Mass customization is a strategy to improve value generation for customers, by offering product variety and, at the same time, maintaining costs and delivery time to an acceptable level. A key problem for applying this strategy in the housebuilding sector is the definition of the solution space, i.e. the range of product alternatives that will be offered. This paper proposes an adaptation of conjoint analysis to identify customer preferences regarding customizable attributes in low-cost housing projects. The utility of this adaptation is illustrated by a case study, which was carried out in a construction company that had delivered low-income housing projects, and offered some degree of product flexibility. Results indicate that this technique was effective to understand customers’ preferences out of a range of housing attributes, by providing a ranking of those attributes chosen by customers. Therefore, this technique can support decision-making when dealing with trade-offs between customers’ preferences, product flexibility and costs, which is an important concern for companies that deliver customized housing units.